PENGUATAN KEWIRAUSAHAAN DAN MANAJEMEN USAHA PADA KOMUNITAS NELAYAN DESA BOKORI - Sudirman Zaid; Juharsah; Wahyuniati Hamid; Harmiaty Bahar; La Harjoprawiro (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to strengthen entrepreneurial capacity and marketing management in the fishing community of Bokori Village, Konawe Regency, Southeast Sulawesi. The main problems faced by partners include low understanding of fishery product branding, minimal knowledge of digital marketing, limited product packaging skills, and weak business management of fishery MSMEs. The implementation method uses a participatory approach through training, mentoring, and hands-on practice involving 30 fishery business actors. The program was implemented for 30 days with activities including branding and product identity training, digital marketing and social media workshops, value-added product packaging training, and business financial management assistance. Program results show significant improvements in understanding branding concepts, ability to use digital platforms for marketing, attractive product packaging skills, and better business financial management. From a marketing management perspective, this program successfully developed a comprehensive marketing mix strategy, created product differentiation through local branding, and opened wider market access through digitalization.